2019
DOI: 10.1097/md.0000000000016069
|View full text |Cite
|
Sign up to set email alerts
|

Better prediction for FGR (fetal growth restriction) with the sFlt-1/PIGF ratio

Abstract: The aim of this study was to check whether the sFlt-1/PIGF ratio, established as the biomarker for preeclampsia, reduces the false positive rate of late fetal growth restriction (FGR) detection by ultrasound biometry. This was a prospective case-control study, conducted at one regional maternity hospital in Romania. Study participants included singleton pregnancy women for whom the estimated fetal weight (EFW) at 28 to 35 weeks was < 10 percentiles and as controls, pregnant women with EFW >10 percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…After adding sFlt1/PIGF ratio to the ultrasound fetal biometry and maternal risk factors, the sensitivity increased to 84.21% with the specificity of 84.31% for a false positive rate of 10%. The authors concluded that when associated with maternal factors and ultrasound biometry, the sFlt1/PIGF ratio enhanced the sensitivity for detecting SGA [9]. Efficacy of sFlt-1/PlGF ratio in FGR prediction was assessed by other researchers as well.…”
Section: Discussionmentioning
confidence: 99%
“…After adding sFlt1/PIGF ratio to the ultrasound fetal biometry and maternal risk factors, the sensitivity increased to 84.21% with the specificity of 84.31% for a false positive rate of 10%. The authors concluded that when associated with maternal factors and ultrasound biometry, the sFlt1/PIGF ratio enhanced the sensitivity for detecting SGA [9]. Efficacy of sFlt-1/PlGF ratio in FGR prediction was assessed by other researchers as well.…”
Section: Discussionmentioning
confidence: 99%
“…5 Visan et al discussed the value of routine ultrasonic examination policy for FGR at 32 weeks gestation, which scored a detection rate of 70% (95% CI, 62%-78%) and the AUC was 0.88. 17 The maternal serum biomarkers are a noninvasive placental biochemical activity analysis aimed for better and earlier detection rates. Researchers investigated different biomarkers for third-trimester screening in a Cochrane systemic review.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of Doppler ultrasound and angiogenic factors (e.g., sFlt-1/PlGF ratio) appears to improve the FGR prediction, as does the combination of fetal biometry and the angiogenic marker 22 , 23 , 24 . However, further studies are still needed before widespread clinical use.…”
Section: Screening Prediction and Preventionmentioning
confidence: 99%
“…Die Kombination der Doppler-Sonografie mit angiogenen Faktoren (z. B. sFlt-1/PlGF-Quotient) scheint die Vorhersage für eine FGR zu verbessern, ebenso wie die Kombination der fetalen Biometrie mit dem angiogenen Marker 22 , 23 , 24 . Allerdings sind auch hier bis zum weiten klinischen Einsatz noch weitere Studien notwendig.…”
Section: Screening Prädiktion Und Präventionunclassified